Pollinating insects on bitter melon plant flowers (Momordica charantia L.) - Oktaviani, Oktaviani; Isnani, Desi (Agrovigor, 2024)
Bitter melon plant (Momordica charantia L.) is a potential commercial plant if intensively cultivated in agribusiness, this plant can be very beneficial if it produces high levels of fruit production, it cannot be separated from insect pollination activities. Insects that visit bitter melon plant flowers are actually beneficial and can be harmful. This field practice aims to determine the relationship of visitor insects associated with bitter melon flowers (M. charantia L.), by using the scan sampling method (direct observation) in the field, which counts the number of species and individual insect’s visitors then will be identified in the Plant Pest Entomology Laboratory. Observations were carried out for 5 weeks. Every week took 2 days of observation, and in those 2 days there were observations on the same day and time which was on Tuesday and Thursday at 06:00: 30 - 08:30 AM (morning) and 04:00 - 05:30 PM (afternoon). What was observed s the insects who visited the bitter melon flowers of 6 orders including Hymenoptera, Coleoptera, Thysanoptera, Lepidoptera, Hemiptera, and Araneae as well as 8 families and 12 species of the orders. Insect visitors associated with bitter melon flowers have different roles including pollinators, predators, visitors and pests. The behavior also varies, especially in taking nectar or pollen as a source of nutrition. Insect visitors associated with bitter melon flowers have different roles including pollinators, predators, visitors and pests. The behavior also varies, especially in taking nectar or pollen as a source of nutrition. Insect visitors associated with bitter melon flowers have different roles including pollinators, predators, visitors and pests. The behavior also varies, especially in taking nectar or pollen as a source of nutrition.